Susceptibility of wild populations of biomphalaria spp. from neotropical South America to schistosoma mansoni and interference of zygocotyle lunata - Spatz, Linus (2012)
Populations of Biomphalaria straminea, Biomphalaria peregrina, Biomphalaria tenagophila, Biomphalaria orbignyi, and Biomphalaria oligoza from different Argentine localities were exposed to miracidia of Schistosoma mansoni EC strain, and Biomphalaria tenagophila, in addition to the SJ2 strain. Biomphalaria straminea and B. tenagophila displayed different susceptibility and compatibility (Frandsen's total cercariae production index class 0-II), whereas B. orbigny and B. oligoza were incompatible. Although B. peregrina and B. tenagophila were found naturally infected with the amphistome Zygocotyle lunata, all 5 species could be experimentally infected with Z. lunata. Exposure to Z. lunata infections with S. mansoni were obtained in natural populations of B. straminea and B. tenagophila with the EC strain (13.5-17.1% and 1.2%), respectively, and in B. tenagophila with the SJ2 strain (2.6%), 60 days postexposure [PE]), and in B. orbignyi and B. oligoza (31.1% and 26.7% 60 days PE, respectively, including single infections with S. mansoni and double infections with Z. lunata). The high susceptibility of B. orbignyi and B. oligoza is noteworthy, as these 2 species are considered resistant to S. mansoni.